Status and trends of biosensor technologies for environmental monitoring of brominated flame retardants - Chiara Sarti; Laura Sforzi; Tania Martellini; Alessandra Cincinelli; Alessandra Cincinelli (Frontiers in Analytical Science)
The persistence of brominated flame retardants (BFRs) in the environment and the associated toxicological risks have made the development of efficient and rapid detection methods increasingly urgent. Despite regulatory mitigation action in many countries, BFRs such as polybrominated diphenyl ethers (PBDEs) and tetrabromobisphenol A (TBBPA) continue to threaten ecosystems due to their resistance to degradation. BFRs persist in air, water, soil, and sediments, and bioaccumulate in the food chain, leading to prolonged exposure risks for both humans and wildlife. Additionally, in regions with less stringent regulations, products containing BFRs are still being manufactured, posing a challenge for customs agencies responsible for regulating imports. This scenario underscores the urgent need for rapid, sensitive, and cost-effective methods to monitor BFRs in commercial products and environmental matrices. Biosensors present a promising solution, offering rapid detection and screening of BFR contamination at trace levels. Their ability to provide accurate, real-time data makes them invaluable for environmental monitoring, product safety, and regulatory compliance. This review explores the recent advancements in biosensor technology for BFR detection, highlighting their potential for improving environmental and human health protection but also underlining the specific areas that require further research.